The Application of Visual Aids in Teaching Academic Writing - Suliman Moamer Adbeeb (Aljameai, 1970)
ABSTRACT:Mostly, we teach with traditional lecture methods. It is hard to get on their habit of writing. It is well known that writing cannot be developed without writing visual aids like Flowchart, Double or Triple Entry. A flowchart image represents the steps and decisions that are made to complete a process. Double or Triple Entry is one more alert brainstorming activity. This is particularly useful when comparing and contrasting two or three topics or when exploring two or three areas of one topic. Through the prewriting method, students make two (or three) columns on their paper. Each column represents a topic which focuses the idea generation. For example, if you are going to compare love and hate, you will being label your columns similarities and differences and list your ideas in the appropriate sections. If your students are writing about their racial heritage in comparison to another, you could have them label one column with each culture. When it completed, students should have a good idea of the points on which they can compare or contrast their topics. Academic writing has unique characteristics in terms of grammatical facial appearance and lexical items. So, it is essential that you start with structure knowledge (characteristics of academic writing and lexical items relevant to the students' courses of study. Secondly, we can start giving a model (text modeling) for the students to be familiar with the format. Next, we can ask the students to write similar texts in groups (joint construction of text) and finally, we can ask them to construct a text individually for assessment.